Quality analysis of a learning media analog electronics on the Android platform with ISO 25010 - Setyanto, Barry Nur; Mushlihudin, Mushlihudin; Pradana, David Yoga (Journal of Vocational Education Studies, 2021)
The design of analog electronics learning media applications needs quality analysis. ISO 25010 is one of the standard references in measuring the quality of an Android-based application product. Analysis that can be done is by testing the compatibility and performance efficiency aspect of the media being developed. This study uses a Research and Development (R&D) method with the ADDIE development model which will produced a quality analog electronics learning media application. Data collection was conducted used a cloud testing and direct testing. Before data collection was conducted validity of media by expert judgement. The results showed that media is "valid" and the quality of the compatibility aspect this media learning was supported on more than 208 smartphones android device and performance efficiency predicate â€œSatisfiedâ€ so that the application could be used for the learning process during the COVID-19 pandemic or tested on other quality aspects.